DAMN: Defeasible Reasoning Tool for Multi-Agent Reasoning - Hecham, Abdelraouf; Croitoru, Madalina; Bisquert, Pierre (Proceedings of the AAAI Conference on Artificial Intelligence, 2020)
This demonstration paper introduces DAMN: a defeasible reasoning platform available on the web. It is geared towards decision making where each agent has its own knowledge base that can be combined with other agents to detect and visualize conflicts and potentially solve them using a semantics. It allows the use of different defeasible reasoning semantics (ambiguity blocking/propagating with or without team defeat) and integrates agent collaboration and visualization features.